Concentrations and variations of total N, available P and K of cultivated soils in Zhejiang Province, China - MA Wan-zhu; ZHANG Ming-kui; LÜ Xiao-nan (浙江大学学报. 农业与生命科学版)
Total N, available P and K of cultivated soils from 11 districts of Zhejiang Province were investigated. Statistical results showed that the average soil total N and available K decreased, and the average soil available P increased, as compared with those obtained at 1980s. The cultivated soil samples with low levels of soil total N (<1 g·kg-1), available P (<10 mg·kg-1) and K (<80 mg·kg-1) accounted for 13.90%, 44.80% and 48.17% of total soil samples, respectively. The proportion of soil samples with deficiency of one of N, P, and K was as high as 73.79%. There were imbalances among soil N, P and K. Great variations in concentrations of soil total N, available P and K were found. The variation coefficients of soil total N, available P and K decreased in the order of available P (192%)> available K (71%) > total N (39%). Soil total N was correlated positively with organic matter, and decreased in the order of clayey soil > clay-loamy soil > loamy soil > sandy soil, and in the order of hydrographic net plain > river plain > hilly area > coastal plain. Soil available P increased with decreasing pH, and decreased in the order of sandy soil > loamy soil > clay loamy soil, clayey soil, and in the order of high hilly area, coastal plain > river plain, low hilly area > hydrographic net plain. Soil available K was related to pH, texture, and geomorphic type, and decreased with decreasing pH. The available K decreased in the order of clayey soil > clay loamy soil > loamy soil > sandy soil, and in the order of coastal plain > hydrographic net plain > river plain > low hilly area > high hilly area.